Gulf Arabic Noun and Verb Retrieval: What Matters? - Tariq Khwaileh (8232351) (2025)
Differential processing between the grammatical classes, i.e., nouns and verbs, has been studied across various linguistic disciplines in different languages, but not Arabic. The present study explores predictors of bare single nouns and bare single verbs in Gulf Arabic through a picture-naming paradigm. Aspects specific to the morpho-phonology of the language (CV skeleton, vocalic pattern) have been investigated for their roles in noun and verb retrieval. A picture-naming paradigm was carried out with 64 healthy native speakers of Gulf Arabic where participants named 282 line drawings representing nouns, and 154 line drawings representing verbs to generate naming latencies for the nouns and verbs in question. Linear regression models were fitted to analyse the relationship between grammatical class and naming latencies as well as morphological features and naming latencies. Verbs, which are more morphologically complex than nouns, were found to have higher naming latencies. Both CV skeleton and vocalic pattern impacted naming latencies and can account for the difference between verb and noun production. The results are discussed in relation to the non-concatenative morphology framework for Semitic languages. Other Information Published in: Journal of Psycholinguistic Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10936-025-10148-2